Mikrostrukturelle Charakterisierung, Modellentwicklung und Simulation poröser Elektroden für Lithiumionenzellen - Ender, Moses (Schriften des Instituts für Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Werkstoffe der Elektrotechnik, 2014)
Electrode microstructures of a high energy and a high power lithium-ion cell were analyzed in 3D using tomographic methods. Calculation of structural parameters enabled a quantitative comparison of the electrodes. To simulate their electrochemical behavior a finite element model was developed which, for the first time, includes a real particle size distribution. This allowed for an identification of the limiting mechanisms during charging and discharging in the electrodes of both cells.